1998
DOI: 10.1016/s0741-5214(98)70055-2
|View full text |Cite
|
Sign up to set email alerts
|

Long-term results after inferior vena caval resection during retroperitoneal lymphadenectomy for metastatic germ cell cancer

Abstract: Only 1 (4.2%) of the patients surveyed had chronic venous sequelae that would fulfill the accepted criteria for subsequent elective IVC reconstruction. Despite recent reports of IVC reconstruction demonstrating relatively good patency rates and low morbidity, the addition of such a complex, time-consuming procedure to extensive retroperitoneal lymph node dissection for metastatic NSGCT involving IVC resection is generally not necessary.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
38
0
5

Year Published

2001
2001
2022
2022

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 90 publications
(43 citation statements)
references
References 23 publications
0
38
0
5
Order By: Relevance
“…The main indications are traumatic or iatrogenic injury, chronic postthrombotic or membranous occlusion, and malignancy, including renal cell carcinoma, 1 Wilms tumor, 2 leiomyosarcoma, 3 adrenal tumor, 4 hepatic carcinoma, 5 and retroperitoneal metastatic lymph nodes from testicular carcinoma. 6 Involvement of large vessels has been considered evidence of advanced disease and a contraindication for resection of abdominal tumors. Indeed, the surgical risks are high and the long-term survival rate is poor.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The main indications are traumatic or iatrogenic injury, chronic postthrombotic or membranous occlusion, and malignancy, including renal cell carcinoma, 1 Wilms tumor, 2 leiomyosarcoma, 3 adrenal tumor, 4 hepatic carcinoma, 5 and retroperitoneal metastatic lymph nodes from testicular carcinoma. 6 Involvement of large vessels has been considered evidence of advanced disease and a contraindication for resection of abdominal tumors. Indeed, the surgical risks are high and the long-term survival rate is poor.…”
Section: Resultsmentioning
confidence: 99%
“…3,6,23 In most patients, circumferential resection of the IVC is necessary to be curative. Lateral resection should not be performed in patients with primary caval tumors with extraluminal extension.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The other cause of the venous sequelae was thought to be that the wide retroperitoneal resection for lymph node dissection concomitant with resection of a segment of the IVC disrupted preexisting venous channels and reduced the collateral venous return. 10) It was reported that deep vein thrombosis occurred after radical resection of the IVC in leiomyosarcoma without replacement in 22 of 82 patients, 11) and in one study, 2 of 8 patients who had the IVC resection for malignant tumors without replacement developed late venous complications, such as edema in the extremities. 8) These results suggest that replacement of the IVC may be benefi cial to patients who undergo extensive retroperitoneal dissection and at least into the SVC system and the use of vasopressor agents reduce excessive hypotension, and the operation can be carried out safely even in the case of suprahepatic IVC clamping.…”
Section: Discussionmentioning
confidence: 93%
“…Although IVC reconstruction has been described, it is a complex, time consuming procedure. On the other hand, IVC resection in young patients is relatively well tolerated and rarely results in any major complications 35 and hence we elected to perform IVC resection when necessary.…”
Section: Discussionmentioning
confidence: 99%